2003
DOI: 10.1051/radiopro:2003020
|View full text |Cite
|
Sign up to set email alerts
|

Voxel anthropomorphic phantoms: review of models used for ionising radiation dosimetry

Abstract: Computational anthropomorphic phantoms have k e n used since the 1970s for dosimetric calculations. Realistic geometries are required for this operation, resulting in the development of ever more accurate phantoms. Voxel phantoms, comisting of a set of smail-volume elements, appeared towards the end of the 1980s, and significantly improved on the original mathematical models. Voxel phantoms are models of the human body, obtained using compnted tomography (CT) or magnetic resonance images (MRI). These phantoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Caon et al (1997Caon et al ( , 1999 developed a voxel phantom of a 14 year old girl, Saito et al (2001) segmented whole-body CT data of a patient whose external dimensions were in good agreement with the Japanese Reference Man (Tanaka 1989), and Xu et al (2000) segmented color photographs of the Visible Human Male (Spitzer and Whitlock 1998) for the construction of the VIPMAN voxel phantom. Comprehensive reviews on the development of voxel-based anthropomorphic phantoms can be found in articles published by Lemosquet et al (2003) and Coan (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Caon et al (1997Caon et al ( , 1999 developed a voxel phantom of a 14 year old girl, Saito et al (2001) segmented whole-body CT data of a patient whose external dimensions were in good agreement with the Japanese Reference Man (Tanaka 1989), and Xu et al (2000) segmented color photographs of the Visible Human Male (Spitzer and Whitlock 1998) for the construction of the VIPMAN voxel phantom. Comprehensive reviews on the development of voxel-based anthropomorphic phantoms can be found in articles published by Lemosquet et al (2003) and Coan (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Adjustments of activity distribution in the phantom were based on 18 F-FDG uptake in the organs of a healthy human. Adjustments of attenuation coefficients for the tissues in the phantom were based on the Zubal phantom (15,16) attenuation coefficients. The phantom was constructed in a 256 · 256 · 256 matrix corresponding to 1.6 mm 3 voxels.…”
Section: Methodsmentioning
confidence: 99%
“…Caon et al (1997Caon et al ( , 1999 developed a voxel phantom of a 14 year old girl, Saito et al (2001) segmented whole-body CT data of a patient whose external dimensions were in good agreement with the Japanese Reference Man (Tanaka et al 1989), andXu et al (2000) segmented colour photographs of the Visible Human Male (Spitzer and Whitlock 1998) for the construction of the VIPMAN voxel phantom. Comprehensive reviews on the development of voxel-based anthropomorphic phantoms can be found in articles published by Lemosquet et al (2003) and Caon (2004).…”
Section: Introductionmentioning
confidence: 99%